(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2016)
هدفت هذه الدراسة إلى البحث عن امكانية وجود علاقة بين نسب السيولة, والكفاية الإدارية, والملاءة المالية, ونسبة الربحية للمصارف الخاصة المدرجة في سوق دمشق للأوراق المالية خلال الفترة (2009-2013). وقامت الدراسة لتحقيق هذه الأهداف بالاعتماد على أساليب التحليل الإحصائي والمالي, حيث تمّ استخدام البرنامج الإحصائي SPSS لتحليل البيانات. كما تمّ حساب التغيرات السنوية لكل نسبة من النسب المدروسة, بالإضافة إلى متوسط معدل النمو خلال الفترة المدروسة, وذلك لكل مصرف من المصارف المدروسة والمدرجة في سوق دمشق للأوراق المالية. بعد التأكد من أن البيانات تخضع للتوزيع الطبيعي بتطبيق اختبار كولموجروف– سميرنوف(K-S), وبالتالي تم دراسة العلاقة بين كل من النسب المدروسة (السيولة, والكفاية الإدارية, والملاءة المالية) وبين الربحية لمعرفة أثر كل من هذه النسب في الربحية, وذلك باستخدام الانحدار البسيط, ومن ثم تحديد النسبة الأكثر تأثيراً على الربحية باستخدام الانحدار المتعدد. وخلصت الدراسة إلى أن العلاقة مابين نسبة السيولة والربحية للمصارف الخاصة هي علاقة عكسية, وكانت العلاقة ما بين نسبة نسبة الكفاية الإدارية والربحية للمصارف الخاصة هي علاقة طردية, بينما كانت العلاقة ما بين نسبة الملاءة المالية والربحية للمصارف الخاصة هي علاقة طردية أيضاً. حيث كانت الملاءة المالية هي النسبة الأكثر تأثيراً في المصارف الخاصة. وهذا ما يؤكد على أن طبيعة عمل المصارف الخاصة قائم على مبدأ العائد والمخاطرة. وأوصت الدراسة إلى توسيع إطار الأبحاث المستقبلية من حيث الحدود الزمانية والمكانية وحجم العينة, وعدم الاقتصار على المصارف الخاصة فحسب، بل أن تشتمل هذه الدراسة على القطاعات الأخرى المدرجة في سوق دمشق للأوراق المالية. وأوصت المصارف الخاصة بالعمل على تنويع استثمارتها بالإضافة إلى التخفيف من السياسة المتحفظة التي تتبعها المصارف. كما أوصت الدراسة المحافظة على مستوى الكفاية الإدارية للمصارف الخاصة وتحسينها من خلال عقد الدورات التدريبية التي ‏من شأنها تحسين إنتاجية الموظفين, وتقليل المصاريف من خلال إدارة أصول المصرف بشكل أفضل.‏ This study aimed to search for the possibility of a relationship between liquidity ratios, administrative efficiency, and financial solvency, and the proportion of private profitability of banks listed on the Damascus Securities Exchange during the period (2009-2013). The study to achieve these goals depending on statistical and financial analysis methods were used to analyze the data SPSS statistical program. As was calculated annual percentage changes for each of the studied descent, in addition to the average growth rate during the period studied, and that each bank of the studied and listed banks in the Damascus Securities Exchange. After making sure that the data are subject to normal distribution application Kolmogerov- Smirnov test (K-S), and thus have been studying the relationship between each of the studied ratios (liquidity, administrative efficiency, and financial solvency) and profitability to see the impact of each of these ratios on profitability, using simple regression, and then the most influential on profitability, the percentage using multiple regression. The study concluded that between the ratio of liquidity and profitability of the privat banks is an inverse relationship, and the relationship between the ratio of administrative efficiency and profitability of the privat banks is a positive correlation, while the relationship between the ratio of financial solvency and profitability of the privat banks is a positive correlation also. Where the solvency ratio is the most influential in the the privat banks. This confirms that the nature of the work of the privat banks based on the principle of return and risk. The study recommended that future research to expand the terms of the framework only temporal and spatial boundaries and the size of the sample, and not only the private banks, but that this study include other sectors listed in the Damascus Securities Exchange. Moreover, recommended that private banks to work to diversify its investments in addition to the mitigation of the conservative policy followed by the private banks. The study recommended maintaining the level of administrative efficiency for private banks and improved through training courses that will improve employee productivity, and reduce expenses through the assets of the bank.